Strategi Pemasaran pada Produk DIY Painting terhadap Peningkatan Pendapatan dengan Memanfaatkan Media Sosial di Era Digital - Maharani Putri Putri Priyani; Nadya Saftitri; Ramadhani Ladysie; Octaviona Cinta Dewi; Wahyu Mashanim Maulida (PUTRA JAWA PUBLISHER, 2025)
An effective marketing strategy is the main key to increasing revenue, especially for creative products such as DIY painting. In the digital era, social media has become a dominant tool to reach consumers widely, quickly, and cost-effectively. This study discusses how social media-based marketing strategies can be implemented to maximize the sales potential of DIY painting products. The main focus is on utilizing platforms such as Instagram, TikTok, and Facebook to build brand awareness, create consumer engagement, and increase sales conversions. With an approach that involves attractive visual content, collaboration with influencers, the use of targeted paid advertising, and intensive interaction with the audience, DIY painting marketing can have a significant impact on increasing revenue. This article also reviews case studies and empirical data that show the effectiveness of social media strategies in supporting the growth of creative businesses in the digital era. As a result, this strategy not only increases sales but also strengthens consumer loyalty and builds a community of DIY painting fans in a sustainable manner.